Perceptions of Pedagogy Lecturers and Students Regarding the Manifestation of Local Wisdom Values - Prihatmojo, Agung; Sartono, E. Kus Eddy; ., Herwin; ., Murjainah; Hamkah, Muh.; Syarif, Irman; Kisworo, Tinto Wahyu; ., Helisman (Journal of Ecohumanism, 2024)
In the realm of education local wisdom has gained recognition as a foundational element for both individual and community growth. This study examines the shared perceptions of local wisdom values among lecturers and pedagogy students in Indonesia, aiming to understand the extent of their consensus and its potential influence on teaching practices. The research employs a descriptive quantitative approach, utilizing a purposive sampling technique that includes 120 students and 10 lecturers. Data collection is conducted primarily through a questionnaire-based survey, with the gathered information subjected to thorough mathematical and statistical analysis. Both descriptive and inferential statistical methods are applied to uncover significant insights. The findings indicate that most students (77.2%) and lecturers (80%) agree on the substantial role of local wisdom values in fostering unity amidst diversity. However, there are perceptual differences influenced by variables such as age, educational background, and life experiences. The study suggests that educational stakeholders should consider these diverse perspectives in curriculum development and teaching methodologies. Despite its limitations, research paves the way for further exploration into the interpretation of local wisdom values in pedagogical practices and their impact on student learning outcomes, as well as their contribution to sustainable development and culturally responsive education policies.